The Determinants of Tourism Industry Competitiveness in Asean Countriesfor the Period 2019-2024 - Fransiskus Handoko; Heru Subiyantoro; Pudji Astuty (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
The tourism industry is a pivotal economic sector for ASEAN countries, significantly contributing to regional GDP and employment. However, the competitiveness of tourism industries across the region has shown considerable variation between 2019 and 2024, influenced by divergent recovery paths from the COVID-19 pandemic and differing national capacities in infrastructure and policy. This study aims to analyze the influence of Tourism Infrastructure, Price Competitiveness, Tourism Policy, and Business Conditions on the competitiveness of the tourism industry in ASEAN countries. The research employed a quantitative approach using panel data regression analysis. The sample covers 10 ASEAN member countries observed annually from 2019 to 2024, with data primarily sourced from the World Economic Forum's Travel & Tourism Development Index (TTDI) and other international databases. The results of the panel data regression indicate that Tourism Infrastructure, Price Competitiveness, Tourism Policy, and Business Conditions collectively have a significant and positive effect on the competitiveness of the tourism industry in the region. Partially, each independent variable also demonstrates a significant positive influence. These findings suggest that improvements in physical infrastructure, attractive pricing, supportive government policies, and a conducive business environment are key determinants in enhancing a nation's tourism competitiveness. The study underscores the necessity for integrated regional strategies and sustained investment in these critical areas to strengthen ASEAN's position as a premier global tourist destination.